2018
DOI: 10.2355/isijinternational.isijint-2017-682
|View full text |Cite
|
Sign up to set email alerts
|

Characteristic Transformation of Manganese-containing Inclusions during Al-killed Process in Ultra-low Carbon Interstitial-free Steel

Abstract: Ferromanganese alloys are usually used for the manganese adjustment to meet the requirement of IF steel grade; and the formation and transformation of manganese-containing inclusions were closely relevant with the recovery yield of manganese in the melt and the morphologies of final deoxidation products. Characteristic transformation of manganese-containing inclusions during Al-killed process in ultra-low carbon interstitial-free steel were studied through the factory trial and hot crucible experiment. Factory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…The characteristics of manganese-containing inclusions during the Al-killed process in interstitial-free steels were studied by Wang et al [89] They found that spherical FeOAExMnO inclusions with sizes below 5 lm existed after an MCFeMn alloy addition. However, almost all these FeOAExMnO inclusions were transformed to Al 2 O 3 inclusions after Al was added to the steel melt.…”
Section: Femn Alloysmentioning
confidence: 99%
“…The characteristics of manganese-containing inclusions during the Al-killed process in interstitial-free steels were studied by Wang et al [89] They found that spherical FeOAExMnO inclusions with sizes below 5 lm existed after an MCFeMn alloy addition. However, almost all these FeOAExMnO inclusions were transformed to Al 2 O 3 inclusions after Al was added to the steel melt.…”
Section: Femn Alloysmentioning
confidence: 99%
“…In addition, compliance with the rational parameters of the metal at tapping from EAF will reduce the contamination of steel with non-metallic inclusions [11][12][13][14][15][16][17][18], as well as reduce the consumption of aluminum for deoxidation of slag in the LF [19][20][21][22].…”
Section: Improving the Technology Of Steel Deoxidation Grade St 37-3mentioning
confidence: 99%
“…The similar results were also reported in other dendritic or clustered inclusions, such as Al 2 O 3 oxides. 18,19) That means the quantifications of number and size of MnS inclusions in 2D observation are imprecise sometimes, and so is their influence on the IPF formation. Therefore, it is more meaningful and necessary to investigate the distribution characteristics of MnS inclusions to evaluate their influence on the IPF formation.…”
Section: Effect Of Mns Inclusions Distribution On Intragranular Ferrimentioning
confidence: 99%